1977
DOI: 10.1042/bj1650199
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the dimensions of the combining sites of the dinitrophenyl-binding immunoglobulin A myeloma proteins MOPC 315, MOPC 460 and XRPC 25 by spin-label mapping

Abstract: The mouse immunoglobulin A myeloma proteins MOPC 315, MOPC 460 and XRPC 25 all possess dinitrophenyl (Dnp)-binding activity. Differences in specificities were shown by measuring the affinities of a variety of haptens. By using a series of Dnp-spin-labelled haptens, the dimensions of the binding sites of the three myeloma proteins were compared by the method described for protein MOPC 315 [Sutton, Gettins, Givol, Marsh, Wain-Hobson, Willan & Dwek (1977) Biochem. J.165, 177-197]. The dinitrophenyl ring is rigidl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1977
1977
1985
1985

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Consequently, for haptens (V) and (VI), only the larger of the two A_,,, values in each case will require allowance for the effect of slow molecular tumbling. This interpretation is supported by a study of hapten binding to another myeloma protein (MOPC 460) and its fragments, in which the site applies no constraints on the hapten's mobility, and A I z is independent of the fragment's size (Willan et al, 1977 Table 4. Maximum hyperfine splittings, A.,., (mT)ofspin-labelledhaptens bound tofragments ofmyelomaprotein MOPC 315…”
Section: Results From Different Fragmentsmentioning
confidence: 88%
See 2 more Smart Citations
“…Consequently, for haptens (V) and (VI), only the larger of the two A_,,, values in each case will require allowance for the effect of slow molecular tumbling. This interpretation is supported by a study of hapten binding to another myeloma protein (MOPC 460) and its fragments, in which the site applies no constraints on the hapten's mobility, and A I z is independent of the fragment's size (Willan et al, 1977 Table 4. Maximum hyperfine splittings, A.,., (mT)ofspin-labelledhaptens bound tofragments ofmyelomaprotein MOPC 315…”
Section: Results From Different Fragmentsmentioning
confidence: 88%
“…In this study there are no marked discontinuities in the e.s.r. spectra between the different haptens, and the binding constants (Willan et al, 1977) show no evidence for such specific interactions.…”
Section: Methods Of Calculation Haptenmentioning
confidence: 91%
See 1 more Smart Citation
“…This value, which is only an approximation, was obtained by adding the maximal distance of the DNP antigen from the 3' hydroxyl of tRNA (about 15 A) to the distance of the 3' end from the anticodon, 76-83 A (25), and subtracting 12 A, which is the distance of the DNP binding site from the periphery of the Ab (26). This relatively long distance may explain why apparent multiple binding sites were found from a supposed single point of attachment.…”
Section: Resultsmentioning
confidence: 99%
“…Proteins M460 and X25 have Kd values of 3.3 gM (Jaffe et al, 1971) and 5,M (Sharon & Givol, 1976) respectively, and might have been expected to behave similarly on the basis of affinity but differently from protein M315, with its Kd of 0.1 pM. Willan et al (1977), in comparing the dimensions of the combining sites of these three proteins by e.s.r. studies on nitroxide spin-labelled Dnp haptens, found that the entrance to the Dnp subsite, presumably the volume occupied by the lysine side chain, was much wider in protein M460 than in either protein X25 or protein M315.…”
Section: Dnp-glymentioning
confidence: 99%